2017
DOI: 10.1099/jmmcr.0.005102
|View full text |Cite
|
Sign up to set email alerts
|

A case of Exophiala dermatitidis infection in a child after allogeneic stem cell transplantation: case report and literature review of paediatric cases

Abstract: Introduction. Exophiala dermatitidisis a relatively common environmental black yeast with worldwide distribution and is a rare cause of fungal infection, mostly in patients with certain predisposing factors. Due to the rarity of the infection, little is known about the specific predisposing factors, way of infection or treatment. Case presentation. Here, we report what is to our knowledge the first case of E. dermatitidis infection in a child after allogeneic stem cell transplantation. We also review all paedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Immunosuppressed and elderly patients suffer from infections with E. dermatitidis most commonly in the form of phaeohyphomycosis, keratitis or chromoblastomycosis; 54 cases of phaeohyphomycosis have been described between 1934 and 2006 (Figure 2) [12,13]. Literature research on recent published case reports involving E. dermatitidis-caused infections revealed 20 new cases since 2007 in both, immunocompetent and -suppressed patients (Table 1) [21,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. E. dermatitidis may also be a severe agent of pneumonia [12].…”
Section: E Dermatitidis Causing Phaeohyphomycosis In Immunosuppressed Patients and Fatal Infections In Immunocompetent Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressed and elderly patients suffer from infections with E. dermatitidis most commonly in the form of phaeohyphomycosis, keratitis or chromoblastomycosis; 54 cases of phaeohyphomycosis have been described between 1934 and 2006 (Figure 2) [12,13]. Literature research on recent published case reports involving E. dermatitidis-caused infections revealed 20 new cases since 2007 in both, immunocompetent and -suppressed patients (Table 1) [21,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. E. dermatitidis may also be a severe agent of pneumonia [12].…”
Section: E Dermatitidis Causing Phaeohyphomycosis In Immunosuppressed Patients and Fatal Infections In Immunocompetent Individualsmentioning
confidence: 99%
“…Currently there are no available standardized broth microdilution methodologies or validated MIC breakpoints for in vitro resistance testing for E. dermatitidis. However, numerous studies dealing with susceptibility patterns of the black yeast-like fungus exist [21,29,41,45,123,130,[132][133][134][135][136][137][138][139][140].…”
Section: Susceptibility and Resistancementioning
confidence: 99%
“…Disseminated infections are extremely rare and probably all associated with inherited immunological diseases such as CARD9 innate immune deficiency [2]. Other predisposing factors for invasive disease include peritoneal dialysis, steroid use, human immunodeficiency virus infection, cancer, bronchiectasis, and diabetes mellitus, demonstrating that numerous changes in patient's condition have been correlated with disease progression [13].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Exophiala dermatitidis infections are very rare in pediatric (14%) and adolescent patients (7%). Hong et al [14] reported a case of liver cirrhosis caused by E. dermatitidis in a previously healthy child, while a pulmonary infection in a child after allogenic stem cell transplantation was reported by Tanuskova et al [13]. Recently, a case of phaeohyphomycosis breast infection in a teenage girl was reported [15].…”
Section: Discussionmentioning
confidence: 99%
“…This dematiaceous (brown-pigmented) fungus is a large, heterogenous group of molds that can cause a wide range of diseases, including phaeohyphomycosis, chromoblastomycosis, and eumycotic mycetoma; however, it is rarely the cause of fungal infection, primarily in patients who already have certain predisposing factors[ 3 , 8 , 14 - 17 ]. It is known to generate a biofilm in a strain-specific manner, with invasive E. dermatitidis isolates forming biofilms with the greatest biomass[ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%